1995
DOI: 10.1007/bf00177781
|View full text |Cite
|
Sign up to set email alerts
|

Activated T lymphocytes in epiretinal membranes from eyes of patients with proliferative diabetic retinopathy

Abstract: Our study demonstrated the involvement of activated immune cells and release of lymphokine(s) in more than half of the diabetic epiretinal membranes tested and revealed that the processes of immune responses and the biological effects of lymphokine(s) may play an important part in the development of epiretinal membranes of PDR, especially in young-onset and type I diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The expression of VCAM-1 in diabetic epiretinal membranes is similar to that of ICAM-1, although in some cases its expression appears to be limited to activated endothelial cells of the neovasculature. [15][16][17][18] Fibrocellular membranes of PVR also express ICAM-1, primarily in highly cellular regions but also within the extracellular matrix. 18,19 The results of these studies suggest a pathogenic role for CAMs in uveitis and in the ultimate development of epiretinal membranes in both PDR and PVR.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of VCAM-1 in diabetic epiretinal membranes is similar to that of ICAM-1, although in some cases its expression appears to be limited to activated endothelial cells of the neovasculature. [15][16][17][18] Fibrocellular membranes of PVR also express ICAM-1, primarily in highly cellular regions but also within the extracellular matrix. 18,19 The results of these studies suggest a pathogenic role for CAMs in uveitis and in the ultimate development of epiretinal membranes in both PDR and PVR.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of epiretinal membranes is still not well understood, but inflammatory and immunological processes are known to be implicated. Several studies of epiretinal membranes showed the presence of activated T lymphocytes, B lymphocytes, and macrophages [1][2][3]. The specific mediators that orchestrate the recruitment of leukocytes leading to proliferative vitreoretinal disorders have not been fully elucidated, although several studies demonstrated elevated levels of several chemokines in vitreous humour removed from patients with proliferative vitreoretinal disorders [4][5][6][7][8].…”
mentioning
confidence: 99%
“…During diabetes, endothelial cells are activated and express high levels of adhesion molecules (12,13). In patients with diabetic retinopathy, levels of soluble intercellular adhesion molecule-1 (ICAM-1) and vascular adhesion molecule-1 (VCAM-1) in the vitreous are drastically enhanced (14), accompanied by increased inflammatory cells, including neutrophils, macrophages, and CD4 ϩ and CD8 ϩ T lymphocytes, in retinal blood vessels (15). Genetic depletion of ICAM-1 or its ligand abolishes retinal leukostasis and protects vascular cells from diabetes-induced apoptosis and vascular leakage (12).…”
mentioning
confidence: 99%